The Influence of Web Quality on Client’s Internet Banking Adoption Mediated by Perceived Ease of Use on Bank Jatim Surabaya - Eriet Erawati; Nurul Aini; Joko Suyono; Damarsari Ratnasahara (IJEBD (International Journal of Entrepreneurship and Business Development), 2020)
Purpose: This paper aims to analyze the influence of web quality on the client’s e-banking adoption through the mediation of perceived ease of use. Design/methodology/approach: The method used is statistic-descriptive and the design used is cross sectional. Findings: 3 out of 7 hypotheses are rejected while the other 4 is accepted. Research limitations/implications: Variables considered in this study are perceived ease of use in technology acceptance model, web quality, accessibility, and internet banking adoption. The samples are a number of customers (60 respondents) in Bank Jatim Surabaya that were chosen using purposive sampling. Practical implications: Results show that the hypotheses proposed are proven by the equation. Originality/value: This paper is original. Paper type: This paper can be categorized as a case study.